ENHANCING THE STUDENTS' CREATIVE WRITING ABILITY THROUGH GENRE AND INTERTEXTUALITY-BASED APPROACH - Sri Mulatsih; Muhammad Rifqi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2012)
It is not an easy task for language students to write creatively. The students usually have insufficient knowledge of what they have to write. In respond to this gap this paper shows how genre and inter-textuality- based approach was implemented to develop the studentsâ€™ creative writing ability through a series of writing assignment. The research participants included 20 students taking â€˜Advanced Genre-Based writingâ€ course in 2010/2011 academic year. The data were obtained from the studentsâ€™ writings and classroom observations. The finding showed that teaching writing using genre and intertextuality approach could enhance the studentsâ€™ creative writing. This evidence could be identified through studentsâ€™ improvements in their Â writingsâ€™ assignments. Another finding revealed that the approach could enhance the studentsâ€™ motivation to express themselves through pieces of Â writings. Based on the findings, the presenters argue that the introduction of genre and inter-textuality to creative writing programs is an important issue that writing teachers should take into account. Keywords: creative writing, genre, intertextuality, studentsâ€™writings, studentsâ€™ motivation